Analysis of blade's chord length with NACA0015 profile for enhanced wave energy conversion of Wells turbine - Huynh, Kha Tuan Tran; Vo, Khoa Anh; Lo, Vay Siu; Truong, Thien Tich (Vietnam Journal of Mechanics, 2025)
This paper investigates the enhancement of Wells turbine blades by modifying the chord length design parameter. The Wells turbine, a promising device in wave energy conversion systems, faces a limited operating range due to flow separation, which restricts its efficiency at higher flow rates. Enhancing the performance of the Wells turbine is crucial for effective wave energy exploitation. The computational simulations in this study are conducted using ANSYS Fluent. Turbine performance is evaluated based on non-dimensional torque, pressure torque, and efficiency, derived from solving the steady 3D incompressible Reynolds Averaged Navier–Stokes equations. The results are validated against reliable references, showing good agreement. The numerical findings reveal that altering the turbine chord length significantly impacts efficiency. Optimizing the chord length enhances the Wells turbine's performance in wave energy conversion, making it a more viable option for renewable energy power generation.